2006
DOI: 10.1128/aem.00891-06
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversity, Localization, and Cell Morphologies of Members of the Candidate Phylum TG3 and a Subphylum in the PhylumFibrobacteres, Recently Discovered Bacterial Groups Dominant in Termite Guts

Abstract: Recently we discovered two novel, deeply branching lineages in the domainHere, we report on the specific detection of these bacteria, the candidate phylum TG3 (Termite Group 3) and a subphylum in the phylum Fibrobacteres, by fluorescence in situ hybridization in the guts of the wood-feeding termites Microcerotermes sp. and Nasutitermes takasagoensis. Both bacterial groups were detected almost exclusively from the luminal fluid of the dilated portion in the hindgut. Each accounted for approximately 10% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 41 publications
12
120
0
Order By: Relevance
“…Among Firmicutes, the abundant population of fermentative bacteria such as members of the orders Clostridiales (represented by Clostridiaceae, Peptococcaceae and Ruminococcaceae) and Lactobacillales (Leuconostocaceae and Enterococcaceae) is consistent with the results of other studies to date on the bacterial community of the termites Hongoh et al 2006). Clostridia and lactic acid bacteria are involved in acetogenesis, sugar degradation and fermentation, and account for the largest diversity in Reticulitermes species (Husseneder et al 2010).…”
Section: Resultssupporting
confidence: 87%
“…Among Firmicutes, the abundant population of fermentative bacteria such as members of the orders Clostridiales (represented by Clostridiaceae, Peptococcaceae and Ruminococcaceae) and Lactobacillales (Leuconostocaceae and Enterococcaceae) is consistent with the results of other studies to date on the bacterial community of the termites Hongoh et al 2006). Clostridia and lactic acid bacteria are involved in acetogenesis, sugar degradation and fermentation, and account for the largest diversity in Reticulitermes species (Husseneder et al 2010).…”
Section: Resultssupporting
confidence: 87%
“…The dominant phylum, the Spirochaetes, comprises 67-71% of the reads in each amplicon data set, followed by the Fibrobacteres (16-25%) and a handful of other phyla each representing 41% of reads, including Proteobacteria, Firmicutes, Bacteroidetes, Acidobacteria and candidate phylum ZB3 (Figure 4). These results are consistent with previous PCR-based (Warnecke et al, 2007) and fluorescence in situ hybridizationbased (Hongoh et al, 2006) profiles of Nasutitermes spp. hindgut communities.…”
Section: Species Evennesssupporting
confidence: 93%
“…In this study, RDA analysis, response ratio, and correlation analysis suggested that members of phyla Spirochaetes, Fibrobacteres, as well as Firmicutes may be the main substrates degraders, e.g., straw-attached TG3 (one candidate class of the phylum Fibrobacteres), and those genera significantly increased at peaks I and II. The TG3 bacteria were mainly found in rumen and wood-feeding termite gut (Hongoh et al 2005;Hongoh et al 2006;Hess et al 2011), which are efficient in transforming plant polymers into sugars and VFAs. Thus, the prevalence of these bacteria associated to straw indicated their dominant roles in the breakdown of plant polymers and supplying soluble substrates for the fermentation and methanogenesis occurring in the slurry.…”
Section: Discussionmentioning
confidence: 99%